2020
DOI: 10.1016/j.celrep.2020.108096
|View full text |Cite
|
Sign up to set email alerts
|

ATR Restrains DNA Synthesis and Mitotic Catastrophe in Response to CDC7 Inhibition

Abstract: Highlights d A CRISPR-Cas9 screen identifies ETAA1 as a determinant of CDC7 inhibitors' potency d CDC7 inhibition causes replication stress and an ATR response requiring ETAA1 d ATR reinforces replication origin firing suppression caused by CDC7 inhibitors d CDC7 and ATR co-inhibition leads to premature and highly defective mitosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 86 publications
(141 reference statements)
12
27
0
Order By: Relevance
“…Analysis of replication tracts showed that cATRi drastically reduces fork elongation rate in U-2OS and HCT116 cells (Figure 1B). Consistent with previous reports showing a role for ATR in repressing origin firing (Buisson et al, 2015;Couch et al, 2013;Moiseeva et al, 2017Moiseeva et al, , 2019Mutreja et al, 2018;Rainey et al, 2020), we found that fork speed was rescued by CDC7 inhibition (Figure 1C). Increased origin firing upon acute ATRi is thought to generate DNA breaks and replication catastrophe in response to HU or aphidicolin (Couch et al, 2013;Toledo et al, 2013).…”
Section: Catri Uncouples Origin Firing and Fork Speed From Genomic Instabilitysupporting
confidence: 93%
See 1 more Smart Citation
“…Analysis of replication tracts showed that cATRi drastically reduces fork elongation rate in U-2OS and HCT116 cells (Figure 1B). Consistent with previous reports showing a role for ATR in repressing origin firing (Buisson et al, 2015;Couch et al, 2013;Moiseeva et al, 2017Moiseeva et al, , 2019Mutreja et al, 2018;Rainey et al, 2020), we found that fork speed was rescued by CDC7 inhibition (Figure 1C). Increased origin firing upon acute ATRi is thought to generate DNA breaks and replication catastrophe in response to HU or aphidicolin (Couch et al, 2013;Toledo et al, 2013).…”
Section: Catri Uncouples Origin Firing and Fork Speed From Genomic Instabilitysupporting
confidence: 93%
“…Consistently, Neutral Comet assay results showed chromosome fragmentation in cells after ionizing radiation but not upon cATRi (Figure 1E). Moreover, we directly compared DSB signaling markers in cells following either cATRi or acute ATRi (aATRi), selecting a AZD6738 dose that was recently used to show a role of ATR in origin firing regulation (Moiseeva et al, 2019;Rainey et al, 2020). Consistent with our results showing the lack of extensive breaks upon cATRi, the signaling response induced by cATRi was markedly different from the response induced by aATRi, which confirmed the expected effect of aATRi in causing DSBs (Figure 1F) (Buisson et al, 2015).…”
Section: Catri Uncouples Origin Firing and Fork Speed From Genomic Instabilitysupporting
confidence: 81%
“…This targets PP1 to pre-RC phospho-sites, acting both negatively on origin activation by counteracting the phosphorylation of MCM by DDK ( 15–17 ), and positively on the licensing step ( 18 ). In metazoans, Rif1 also modulates cellular responses and suppresses DNA replication after the inhibition of Cdc7 ( 19 ), and Rif1 bound to the nuclear lamina regulates replication firing time as a possible organiser of chromatin architecture ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anomalous mitotic entry before the completion of DNA replication may result in mitotic catastrophe and is correlated with multipolar spindle and giant, multinuclear cells. 39 In addition, mitotic catastrophe is a non-lethal process, but it includes a crossroad that might drive cells into necrosis or apoptosis, 40 and the inhibition of apoptosis may mitigate asymmetrical division and the aneuploid cell generation. 41 Our study indicated that the increased apoptotic rate of HG-treated cells was an outcome of both podocyte injury and mitotic catastrophe.…”
Section: Discussionmentioning
confidence: 99%